Enhancing effect of lysine combined with other compounds on cephamycin C production in Streptomyces clavuligerus - Leite, Carla A. [UNESP]; Cavallieri, Andre P. [UNESP]; Araujo, Maria Lucia Gonsales da Costa [UNESP] (Biomed Central Ltd., 2013)
Background: Lysine plays an important role in Streptomyces clavuligerus metabolism; it takes part in its catabolism, via cadaverine, and in its secondary metabolism, in which lysine is converted via 1-piperideine-6-carboxylate to alpha-aminoadipic acid, a beta-lactam antibiotic precursor. The role of lysine as an enhancer of cephamycin C production, when added to production medium at concentrations above 50 mmol l(-1), has already been reported in the literature, with some studies attributing a positive influence to multifunctional diamines, among other compounds. However, there is a lack of research on the combined effect of these compounds on antibiotic production.Results: Results from experimental design-based tests were used to conduct response surface-based optimization studies in order to investigate the synergistic effect of combining lysine with cadaverine, putrescine, 1,3-diaminopropane, or alpha-aminoadipic acid on cephamycin C volumetric production. Lysine combined with cadaverine influenced production positively, but only at low lysine concentrations. On the whole, higher putrescine concentrations (0.4 g l(-1)) affected negatively cephamycin C volumetric production. In comparison to culture media containing only lysine as additive, combinations of this amino acid with alpha-aminoadipic acid or 1,3-diaminopropane increased cephamycin C production by more than 100%.Conclusion: This study demonstrated that different combinations of lysine with diamines or lysine with alpha-aminoadipic acid engender significant differences with respect to antibiotic volumetric production, with emphasis on the benefits observed for lysine combined with alpha-aminoadipic acid or 1,3-diaminopropane. This increase is explained by mathematical models and demonstrated by means of bioreactor cultivations. Moreover, it is consistent with the positive influence of these compounds on lysine conversion to alpha-aminoadipic acid, a limiting step in cephamycin C production.
Keywords: Streptomyces clavuligerus; Cephamycin C; Lysine; Diamines; Alpha-aminoadipic acid; Response surface